2015
DOI: 10.1038/srep18056
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl Cellulose Based Non-Volatile Gel Polymer Electrolytes for Dye-Sensitized Solar Cell Applications using 1-methyl-3-propylimidazolium iodide ionic liquid

Abstract: Gel polymer electrolytes using imidazolium based ionic liquids have attracted much attention in dye-sensitized solar cell applications. Hydroxypropyl cellulose (HPC), sodium iodide (NaI), 1-methyl-3-propylimidazolium iodide (MPII) as ionic liquid (IL), ethylene carbonate (EC) and propylene carbonate (PC) are used for preparation of non-volatile gel polymer electrolyte (GPE) system (HPC:EC:PC:NaI:MPII) for dye-sensitized solar cell (DSSC) applications. The highest ionic conductivity of 7.37 × 10−3 S cm−1 is ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…EC and PC combination is a high dielectric constant material generally used for the preparation of gel electrolytes to improve conductivity and maintain gel‐like state even at low temperature. This combination is generally used in the preparation of gel electrolytes …”
Section: Resultsmentioning
confidence: 99%
“…EC and PC combination is a high dielectric constant material generally used for the preparation of gel electrolytes to improve conductivity and maintain gel‐like state even at low temperature. This combination is generally used in the preparation of gel electrolytes …”
Section: Resultsmentioning
confidence: 99%
“…The main advantages of ionic liquids over organic solvents are low vapor pressure, high ionic conductivity, good chemical and thermal stability, non-flammability, as well as wide electrochemical stability window [6][7][8]. The imidazolium iodide-based ionic liquids are widely used in DSSC as it may play the roles of both conductive medium and nonvolatile plasticizers in electrolytes as well as provide better performance in dye-sensitized solar cells [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is an improvement on the stability of DSSCs using GPEs, it is found that the photovoltaic performance of GPE based DSSCs is lower compared to the liquid electrolytes based DSSCs. This is because of the gel network that holds back the charge carriers in the gel electrolytes to a certain area and the gelatinization which might react with other components of the electrolytes which cause a decrease in the gel electrolytes performance …”
Section: Introductionmentioning
confidence: 99%